Investigation of Steady Fluid Flow in Pre-Screen Zone of Well During Its Regeneration while Using Tube Post-Filter Flushing - V. V. Ivashechkin (Izvestiâ Vysših Učebnyh Zavedenij i Ènergetičeskih ob Edinennij SNG. Ènergetika, 2013)
The paper describes a steady pressure and free-flow circulation flow in the pre-screen zone of a well during its hydrodynamic reagent-free flushing. Calculation dependences for description of a filtration flow and creation of a hydrodynamic grid have been obtained in the paper. The paper presents results of experimental investigations on filtration flow. The obtained results agree completely with the calculation dependences that testifies about the possibility to use the obtained formulas for description of the filtration flow originating in the pre-screen zone of a well during its hydrodynamic reagent-free flushing.